Homocysteine and Psychiatric Disorders - Silva,Vanessa Cavalcante da (2017)
Abstract Psychiatric disorders are highly prevalent all over the world with a great impact on public health. Altered homocysteine metabolism is implicated in the pathogenesis of many of these disorders, as it can interfere in normal methylation of subcellular components, promote neuroexcitotoxicity, and induce oxidative stress and inflammation. There are cumulative data implicating these mechanisms in the development of autism, schizophrenia, depression, bipolar disorder, and Alzheimer disease. Altered homocysteine metabolism is multifactorial in its origin. On one hand, genetic factors act as predisposing factors through brain development and function, and on the other hand, environmental factors give the opportunity for nutritional interventions improving metabolic status and possibly also clinical parameters. This article provides a review on the association of 1-carbon metabolism and autism, schizophrenia, depression, bipolar disorder, and dementia and goes through studies on the role of different cofactors and metabolites involved in this pathway.